Implementation of Electronic System based on Notary Administration - Wulandari, Rezekista; Bawono, Bambang Tri (Jurnal Konstatering, 2022)
This study aims to (1) identify and understand the implementation of electronic-based Notary Administration in the conception of legal certainty. (2) knowing and understanding the effectiveness of electronic-based administrative system management. This research is descriptive with a sociological juridical approach. The data collected in the form of primary data and secondary data. Data was collected through field studies and literature studies. Data were analyzed by quantitative descriptive. The results of the study show that (1) the Implementation of Electronic-Based Notary Administration provides legal certainty guarantees if there are no conflicting provisions between one law and another (2) Effectively Management of the Electronic-Based Notary Administration System is economical, electronic notary protocol storage aims to be more practical, efficient, inexpensive and secure. Meanwhile, from the legal aspect, it can help and facilitate the legal process related to the law of evidence, namely electronic evidence.